2013
DOI: 10.1111/ppl.12085
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a gene encoding β‐ureidopropionase is critical for pollen germination in tomatoes

Abstract: Global warming has seriously decreased world crop yield. High temperatures affect development, growth and, particularly, reproductive tissues in plants. A gene encoding β-ureidopropionase (SlUPB1, EC 3.5.1.6) was isolated from the stamens of a heat-tolerant tomato (CL5915) using suppression subtractive hybridization. SlUPB1 catalyzes the production of β-alanine, the only β-form amino acid in nature. In the anthesis stage, SlUPB1 expression in CL5915 stamens, growing at 35/30°C (day/night), was 2.16 and 2.93 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
1
1
0
1
Order By: Relevance
“…The inhibition of tomato pollen germination between 37 and 40°C is in line with previous publications demonstrating that a treatment of 38°C negatively affects pollen germination in tobacco and tomato [29,59,60]. The ability of tomato pollen to germinate after long-term storage or heat stress depends on the biosynthesis of polyamines [60,61], or β -alanine [62] with a role for specific amino acid transporters during de-/hydration phases [63]. In tobacco ( Nicotiana tabacum ) pollen specific peptides are dephosphorylated during pollen activation [28].…”
Section: Discussionsupporting
confidence: 87%
“…The inhibition of tomato pollen germination between 37 and 40°C is in line with previous publications demonstrating that a treatment of 38°C negatively affects pollen germination in tobacco and tomato [29,59,60]. The ability of tomato pollen to germinate after long-term storage or heat stress depends on the biosynthesis of polyamines [60,61], or β -alanine [62] with a role for specific amino acid transporters during de-/hydration phases [63]. In tobacco ( Nicotiana tabacum ) pollen specific peptides are dephosphorylated during pollen activation [28].…”
Section: Discussionsupporting
confidence: 87%
“…Pollen viability has been recently used to identify heat-tolerant tomato genotypes, indicating pollen thermo-tolerance as an important parameter to consider for future breeding programs. Shen et al [19] indicated that the β-alanine plays a role in pollen germination under high temperatures. It is possible that the high concentration of this molecule, which is the third most representative free amino acid contained in the biostimulant (Table S3), was responsible for the higher pollen viability found in the biostimulant-treated plants.…”
Section: A Protein Hydrolysate-based-biostimulant Protects Pollen Viability From Drought-induced Desiccationmentioning
confidence: 99%
“…Alguns estudos detectaram sua presença em folhas de tabaco, feijões, nozes, sementes de melancia, ervilhas, cevada, tomates e cenouras (Widodo et al, 2009;Leiss et al, 2013;Shen et al, 2014). No entanto, o conteúdo de β-alanina nesses alimentos é extremamente baixo, podendo ser negligenciado para fins de quantificação de seu consumo via dieta.…”
Section: Fontes Alimentaresunclassified